Respons Aplikasi Melatonin dalam Proteksi Tingkat Kerusakan Organ Floral, Gametofit, dan Karakter Biokimia Biji Selama Cekaman Kromium pada Padi - Nirmala Rossalina Sujono (Fakultas Pertanian, 2026)
Chromium (Cr) is a non-essential heavy metal that has had a massive toxic impact on cultivated plants, especially rice. Melatonin as an anti-stress agent can act as an antioxidant and metal chelator can be a solution to increase plant tolerance to Cr toxicity. This study aims to examine the response of melatonin application in protecting floral organs, gametophytes, and biochemical characteristics of rice seeds (Oryza sativa L. var. IR64) against chromium stress (Cr 100 mg/L). The study used a Completely Randomized Design (CRD) with 6 treatments (control, single Cr, Cr + melatonin 25-100 mg/L) and 3 replications, conducted at the Agrobiotechnology Laboratory and Greenhouse, University of Jember from July 2025 to April 2026. Cr stress caused a significant decrease in plant height, pollen fertility, number of full seeds, and chlorophyll, amylose, protein, and seed lipid content. Melatonin application at a dose of 100 mg/L was most effective in restoring vegetative morphological parameters (plant height, root length), reproductive parameters (pollen sterility, panicle number), and seed biochemistry to those of control conditions. However, RAPD analysis showed low DNA polymorphism, indicating that the effects of Cr+melatonin were more dominant in physiology than in genetic damage. Melatonin at 100 mg/L proved optimal as a protective agent against Cr toxicity in the generative phase of rice.
FINALISASI oleh Arif 2026 Juni 04
Keywords: Melatonin; Kromium; Padi IR64; Organ Floral; Biokimia Biji; Stres Logam Berat